Handsome Devils: Mobile imaginings of Youth Culture - Crawford, Kate; Goggin, Gerard (Global Media Journal - Australian Edition, 2008)
Mobile technologies are becoming central to contemporary media — yet there has been little critical examination of mobiles, or of their role in community, alternative, and citizens’ media. Accordingly, in this paper we examine the way that mass media representations of mobile media are bound up with individualistic interpretations of youth culture. Advertising campaigns herald a new era of youthful mobile media interactions, from glamorous 20-somethings silhouetted with their iPods to teenagers sending flirtatious text messages. At the other end of the spectrum, familiar youth panics are being translated into technological iterations, continuing “the unhappy marriage of youth and media theory” (Ishita, 1998). We argue such narratives form a larger picture of what we call ‘seductive and destructive’ mobile imaginaries. Youth culture is often a site upon which broader social concerns are projected, and the current mobile imaginaries reveal the affective patterns of anxiety and desire that mark popular representations of youth and technology. A critical understanding of such imaginaries helps locate the ‘our’ in mobile media, and so articulate sustainable media and cultural futures.